"That was the Last Time I Saw my House": The Importance of Place Attachment among Children and Youth in Disaster Contexts. Issue 1 (26th July 2016) - Scannell, Leila; Cox, Robin S.; Fletcher, Sarah; Heykoop, Cheryl
Abstract: Place attachment is important for children and youth's disaster preparedness, experiences, recovery, and resilience, but most of the literature on place and disasters has focused on adults. Drawing on the community disaster risk reduction, recovery, and resilience literature as well as the literature on normative place attachment, children and youth's place‐relevant disaster experiences are examined. Prior to a disaster, place attachments are postulated to enhance children and youth's disaster preparedness contributions and reinforce their pre‐disaster resilience. During a disaster, damage of, and displacement from, places of importance can create significant emotional distress among children and youth. Following a disaster, pre‐existing as well as new place ties can aid in their recovery and bolster their resilience moving forward. This framework enriches current theories of disaster recovery, resilience, and place attachment, and sets an agenda for future research.